A comparison between the anxiety and hope in mothers having children suffering from autism syndrome and Down syndrome - Maryam Mokhtari Mosayebi (Report of Health Care, 2015)
Introduction: The present research aimed to compare anxiety and hope between mothers having children suffering from autism syndrome and Down syndrome. Methods: This research used a descriptive-comparative method and the sample of the study included 60 mothers having children suffering from autism and down syndromes. The sample was selected among all mothers having children in the age of 6-12 who were suffering from autism and Down syndrome in Kerman in 2014. In order to measure the variables of the research we used 2 questionnaires, the Pennsylvania anxiety questionnaire and the scale of aptitude toward hope among adults. Results: The results showed that the amount of anxiety and hope among mothers having children suffering from autism was different from mothers having children suffering from Down syndrome. Conclusion: The anxiety between mothers having children with autism syndrome was more than mothers having children with Down syndrome. The level of hope between mothers having children with Down syndrome was higher than mothers having children with autism syndrome.